"Do Not Harm the Decorum": Mixed Courts and Cloth in Colonial Indonesia. (August 2022) - Ravensbergen, Sanne
Abstract : In this article four photographs of mixed law courts (landraad) in nineteenth-century colonial Indonesia are approached as a window to study the materiality and meaning of cloth in courtrooms. The photos grant access to a careful colonial curation as well as complex Javanese hierarchies that were translated onto and through cloth, and its colors and patterns. Batik sarongs, tablecloths, head scarves, robes and gowns, coats and turbans reveal a courtroom of semiotic richness and plurality where different actors were signaling different messages to multiple audiences. This emphasis on cloth contributes to an emergent and rich discussion on the importance of objects in the study of law and empire, that has primarily focused on the materiality of paper and other objects of lawmaking. In the mixed court of the landraad, it was cloth that spoke louder than words and paper. This article emphasizes that in a mixed court the display of a plural world and jurisdictional layering, complicating the binary between direct and indirect colonial rule, was more important than a monolithic reflection of state law. Cloth was crucial to the display of this plural world and used as a way to impose, maintain, alter, insert oneself in or resist colonial rule.